Practice of Corpse Management Using Props - Anisa Destiani; Imam Tabroni; Scherschligt Oscar; Morse Kathryn (Yayasan Adra Karima Hubbi, 2023)
Background. Learning in the classroom One of the factors that most determines the success of the learning process in the classroom is the learning method An ideal learning process is when in the learning process the teacher is able to activate students to develop their assumptions in building a perception related to the competencies or material to be learned. There are many kinds of learning methods. Purpose. one of the methods used to improve the skills of female students in taking care of the corpse is using the demonstration method. Method. the practice method is a learning method to train female students with the aim of increasing the ability of female students to apply the knowledge and skills that have been learned. Results. practice method is a learning method to train female students with the aim of increasing the ability of female students to apply the knowledge and skills that have been learned. Conclusion. Meanwhile, according to Roestiyah, the practice method is a way of teaching students through direct practice in the field by involving students actively in activities in the field.